The Reassessing State Loss Calculations: Limited Authority of BPKP & Public Accountant Findings in Corruption Cases - Sulistyowati Sulistyowati; Haniff Ahamat; Rumainur Rumainur; Dewi Nadya Maharani (Unissula, 2026)
@font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536870145 1107305727 0 0 415 0;@font-face font-family:Aptos; panose-1:2 11 0 4 2 2 2 2 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 3 0 0 415 0;@font-face font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-520081665 -1073717157 41 0 66047 0;p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; mso-pagination:none; text-autospace:none; font-size:11.0pt; font-family:"Times New Roman",serif; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-US;.MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; font-family:"Aptos",sans-serif; mso-ascii-font-family:Aptos; mso-fareast-font-family:Aptos; mso-hansi-font-family:Aptos; mso-bidi-font-family:Arial; mso-font-kerning:0pt; mso-ligatures:none;div.WordSection1 page:WordSection1; The determining state losses in corruption cases is often a crucial issue that poses a significant legal challenge, despite corruption being categorized as a serious crime. This research aims to investigate the determination of state losses and analyze its impact on the principle of legal certainty. This research uses normative legal methods with a qualitative approach. The results of the study indicate a normative deviation, where judges frequently affirm state loss reports from institutions outside the regulated authority, such as Financial and Development Supervisory Agency or public accountants. This practice is fundamentally contrary to Audit Board of the Republic of Indonesia legal standing as stipulated in the Law on the Eradication of Corruption and its amendments. Because only the Audit Board of the Republic of Indonesia can determine actual state losses and potential state losses that could become actual state losses as a result of corruption crimes that occur. The implication of this deviation is grave legal uncertainty, potentially undermining the fundamental rights of suspects or defendants, and undermining the integrity of the criminal justice system.